Investigation the effect of job satisfaction factors on safety in civil project - Mohammad Javad Abdolahi; Behnod Barmayehvar (مهندسی و مدیریت ساخت, 2017)
Undoubtedly, the construction industry is one of the most dangerous industries in terms of injuries and human casualties. One of the most important reasons for accidents was the lack of identification of the causes of doing dangerous work and the non-observance of safety issues, so identifying and analyzing the factors that cause construction workers to take high-risk jobs is a very important step. To secure the workshop. One of the most important causes that can lead to high-risk activities is the high-risk worker involved in the project. Since the source of work stress is job dissatisfaction, it is crucial to examine this issue. But the important thing is that job satisfaction is a general concept; in other words, job satisfaction will be achieved by realizing a set of factors. Therefore, in this research, we tried first to identify the factors affecting job satisfaction separately. Then a questionnaire was prepared for 70 people working in three development workshops. Using a fuzzy method, the importance of each of the above factors was scored. In the end, by means of a hierarchical analysis method, ranking criteria and the most important factor are identified. Meanwhile, with suggestions to control the very important factors, it is possible to prevent the occurrence of accidents in development projects.